Silica-coated upconversion lanthanide nanoparticles: The effect of crystal design on morphology, structure and optical properties - Kostiv, Uliana; Šlouf, Miroslav; Macková, Hana; Zhigunov, Alexander; Engstová, Hana; Smolková, Katarína; Ježek, Petr; Horák, Daniel (Beilstein journal of nanotechnology, 2015)
NaYF4:Yb(3+)/Er(3+) nanoparticles were synthesized by thermal decomposition of lanthanide trifluoroacetates using oleylamine (OM) as both solvent and surface binding ligand. The effect of reaction temperature and time on the properties of the particles was investigated. The nanoparticles were characterized by transmission electron microscopy (TEM), electron diffraction (ED), energy dispersive spectroscopy (EDX), dynamic light scattering (DLS), thermogravimetric analysis (TGA), elemental analysis and X-ray diffraction (XRD) to determine morphology, size, polydispersity, crystal structure and elemental composition of the nanocrystals. TEM microscopy revealed that the morphology of the nanoparticles could be fine-tuned by modifying of the synthetic conditions. A cubic-to-hexagonal phase transition of the NaYF4:Yb(3+)/Er(3+) nanoparticles at temperatures above 300 °C was confirmed by both ED and XRD. Upconversion luminescence under excitation at 980 nm was observed in the luminescence spectra of OM-NaYF4:Yb(3+)/Er(3+) nanoparticles. Finally, the OM-NaYF4:Yb(3+)/Er(3+) nanoparticles were coated with a silica shell to enable further functionalization and increase biocompatibility and stability in aqueous media, preventing particle aggregation.
Keywords: lanthanide; oleylamine; upconversion; silica; nanoparticles